The optimum embedded controller for handheld electronic nose - Abu Hassan, Abdullah; Abdul Hamid, Adom, Prof. Madya Dr.; Ali Yeon, Md Shakaff, Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr.; Ammar, Zakaria; Fathinul Syahir Ahmad, Sa'ad (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.